If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(3 + -7x) + 4(3 + -1x) = 7x + -3(x + -1) 2x + (3 * -1 + -7x * -1) + 4(3 + -1x) = 7x + -3(x + -1) 2x + (-3 + 7x) + 4(3 + -1x) = 7x + -3(x + -1) 2x + -3 + 7x + (3 * 4 + -1x * 4) = 7x + -3(x + -1) 2x + -3 + 7x + (12 + -4x) = 7x + -3(x + -1) Reorder the terms: -3 + 12 + 2x + 7x + -4x = 7x + -3(x + -1) Combine like terms: -3 + 12 = 9 9 + 2x + 7x + -4x = 7x + -3(x + -1) Combine like terms: 2x + 7x = 9x 9 + 9x + -4x = 7x + -3(x + -1) Combine like terms: 9x + -4x = 5x 9 + 5x = 7x + -3(x + -1) Reorder the terms: 9 + 5x = 7x + -3(-1 + x) 9 + 5x = 7x + (-1 * -3 + x * -3) 9 + 5x = 7x + (3 + -3x) Reorder the terms: 9 + 5x = 3 + 7x + -3x Combine like terms: 7x + -3x = 4x 9 + 5x = 3 + 4x Solving 9 + 5x = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9 + 5x + -4x = 3 + 4x + -4x Combine like terms: 5x + -4x = 1x 9 + 1x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 9 + 1x = 3 + 0 9 + 1x = 3 Add '-9' to each side of the equation. 9 + -9 + 1x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 3 + -9 1x = 3 + -9 Combine like terms: 3 + -9 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 4w-4x-y+3w+18x-8y= | | 2x+8=3-2x | | 1=9-3 | | T-(x-8)=-2 | | 18P-226=48 | | (x-4)(x^2+3)-(x-4)(6x-2)=0 | | -10+4x=2x-16 | | 70=10u | | 5x/95 | | 13+4(x+3)=105 | | 5+3A=7A-56 | | 3a+5=4 | | 2x^2+5x+(3-3k)=0 | | n^2-22n+40=0 | | 10x-2y+10w+7y-3w+4c= | | 17=15+w-5 | | 3(2X-4)=X+3 | | 6m-10=28 | | 9x-1=63-7x | | 3k+6=14 | | (x-3)(y+5)=xy-19 | | 4n^2=-6n-1 | | y=0.2x^2+0.15x+0.8 | | 3c-1=c+a | | 2H-32=5H-7 | | 3sin^2x=cosx | | -2x-6=5x-10 | | 7y=-3x+4 | | 4//4/5 | | 57=9p+3 | | 4w+4y+8x+6x-13y+4w= | | 7-3A=19 |